BETWEEN PHILOLOGY AND CRITICISM IN LITERARY TRANSLATION: LA COSCIENZA DI ZENO BY ITALO SVEVO - di Nunzio, Novella (Vertimo studijos, 2017)
The aim of this article is to present some theoretical reflections on the matter of literary translation by referring to two different methodological approaches: philology and criticism. The analysis is conducted on La coscienza di Zeno by Italo Svevo, one of the most relevant novels of Italian Modernism, and focuses on two paratextual aspects that, in connection with the translation of a literary text, are of particular significance: the choice of the reference text, which is linked to philology; and the strategy for title translation, which is linked to criticism.